2020
DOI: 10.12973/ijem.6.4.681
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Procrastination on Academic Achievement: A Meta-Analysis Study

Abstract: The aim of the present study is to examine the effect level of procrastination on academic achievement. To this end, a meta-analytic approach was applied and the studies published between January 2000 and May 2020 in Education Resources Information Center (ERIC) and Academic Search Ultimate databases were included in the study. The research was limited to articles examining the correlation between the variables and, accordingly, the correlation coefficient was specified as an index to identify the effect size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
2
5
0
3
Order By: Relevance
“…Academic procrastination has been found to be associated with negative academic outcomes, such as delays in submitting assignments and preparing for exams, resulting in low scores (Beswick, Rothblum, & Mann, 1988;Semb, Glick, & Spencer, 1979). This is in line with the results of a meta-analysis conducted by some researchers that show academic procrastination has a significant negative relationship with academic achievement (Akpur, 2020;Kim & Seo, 2015;Steel & Ferrari, 2013). Therefore, it is important to do further research on the relationship between academic procrastination and academic achievement in order to identify categories and directions of the relationship among the students as the research subjects.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Academic procrastination has been found to be associated with negative academic outcomes, such as delays in submitting assignments and preparing for exams, resulting in low scores (Beswick, Rothblum, & Mann, 1988;Semb, Glick, & Spencer, 1979). This is in line with the results of a meta-analysis conducted by some researchers that show academic procrastination has a significant negative relationship with academic achievement (Akpur, 2020;Kim & Seo, 2015;Steel & Ferrari, 2013). Therefore, it is important to do further research on the relationship between academic procrastination and academic achievement in order to identify categories and directions of the relationship among the students as the research subjects.…”
Section: Introductionsupporting
confidence: 82%
“…The results show that academic procrastination has a significant but negative effect on academic achievement. It is relevant to previous studies that found a significant negative relationship between academic procrastination and academic achievement (Akpur, 2020;Goroshit, 2018;Kim & Seo, 2015;Nwosu, Okoyoe, & Onah, 2018;Wu & Fan, 2017;You, 2015). A significant and negative relationship means that if students experience academic procrastination, it will be followed by declining academic achievement.…”
Section: Discussionmentioning
confidence: 89%
“…Erteleme, bir durum konusunda karar vermede, sorumluluk almada ya da bir görevi tamamlamada gecikme veya bunu daha sonraki bir tarihe öteleme davranışı olarak tanımlanmaktadır (Atamtürk, Çalık Var ve Gökler, 2020;Bulut, 2014;Durgun, Kalyoncuoğlu ve Avcı 2021;Naktiyok ve Kızıl, 2018;Seyfi, 2019). Ertelemeyi, bireylerin görevleri başlatmasını veya tamamlamasını engelleyebilecek bir şeyi kasıtlı olarak erteleme eylemi olarak tanımlamak da mümkündür (Akpur, 2020;Daryani, Nugrahayu ve Sulistiawat, 2021;Ghaffari ve diğerleri, 2021;Karabıyık Çeri, Çavuşoğlu ve Gürol, 2015;Naktiyok ve Kızıl, 2018;Seyfi, 2019). Ertelemede, insanlar bir işi tamamlama düşüncesini somut bir duruma dönüştürmek için yeterince performans gösteremezler ve bu nedenle, bir durum oluştuğunda, görevi tamamlama yeteneği sadece düşünce düzeyinde kalır.…”
Section: Introductionunclassified
“…Yapılması amaçlanan davranış ile fiilen sergilenen davranış arasında tutarsızlık ortaya çıkar (Yaraş, 2021). Yaşamın hemen hemen tüm alanlarında erteleme davranışı görülebilmektedir (Abdi Zarrin, Gracia ve Paixão, 2020;Akpur, 2020;Durgun, Kalyoncuoğlu ve Avcı 2021;Guo ve diğerleri, 2019;Kaplan, 2017;Karabıyık Çeri, Çavuşoğlu ve Gürol, 2015;Seyfi, 2019). Erteleme davranışı literatürde, genel erteleme, karar vermeyi erteleme, kompulsif erteleme (karar verme ve yapılması gerekli olan işleri ertelenme), nevrotik erteleme (ciddi ve önemli konularda karar vermede erteleme eğilimi) ve akademik erteleme olmak üzere dört ana başlık altında incelenmiştir (Abdi Zarrin, Gracia ve Paixão, 2020;Akpur, 2020;Durgun, Kalyoncuoğlu ve Avcı, 2021;Kaplan, 2017;Karabıyık Çeri, Çavuşoğlu ve Gürol, 2015;Seyfi, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation